Enhancing Effects of Environmental Enrichment on the Functions of Natural Killer Cells in Mice - Xiao, Run; Ali, Seemaab; Caligiuri, Michael A.; Cao, Lei (Frontiers in Immunology, 2021)
The environment of an organism can convey a powerful influence over its biology. Environmental enrichment (EE), as a eustress model, has been used extensively in neuroscience to study neurogenesis and brain plasticity. EE has also been used as an intervention for the treatment and prevention of neurological and psychiatric disorders with limited clinical application. By contrast, the effects of EE on the immune system are relatively less investigated. Recently, accumulating evidence has demonstrated that EE can robustly impact immune function. In this review, we summarize the major components of EE, the impact of EE on natural killer (NK) cells, EE’s immunoprotective roles in cancer, and the underlying mechanisms of EE-induced NK cell regulation. Moreover, we discuss opportunities for translational application based on insights from animal research of EE-induced NK cell regulation.